2016
DOI: 10.1080/20477724.2016.1258163
|View full text |Cite
|
Sign up to set email alerts
|

Para-kala-azar dermal Leishmaniasis cases in Indian subcontinent – A case series

Abstract: Case summaryHere, we are presenting a series of nine cases; who were residents of Bihar, India. The details of clinical features,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…In this study, most of the patients were aged between 18-45 years which is similar to an Indian case series where 6 out of 9 patients were under this age group [9]. The average body temperature and spleen size were, however, higher than that of the Indian case series.…”
Section: Plos Onesupporting
confidence: 80%
See 2 more Smart Citations
“…In this study, most of the patients were aged between 18-45 years which is similar to an Indian case series where 6 out of 9 patients were under this age group [9]. The average body temperature and spleen size were, however, higher than that of the Indian case series.…”
Section: Plos Onesupporting
confidence: 80%
“…The average body temperature and spleen size were, however, higher than that of the Indian case series. Most of the patients presented with macular type PKDL-like lesions-which is the most common type in the Indian subcontinent and resembles other studies as well [9,10].…”
Section: Plos Onesupporting
confidence: 62%
See 1 more Smart Citation
“…We found 2 unusual cases of concomitant PKDL and VL in the community which is recently termed as para kala-azar dermal leishmaniasis. A series of 9 cases described by Kumar et al 13 indicates that para kala-azar dermal leishmaniasis is not very uncommon in endemic areas. Our survey showed that kala-azar was verging on a greater proportions and appearance of such an outbreak is serious because of the risk of spread to other areas.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of our patient, who faced both the variants, a treatment protocol was planned from both the guideline and insights from previous reports. A case series was found from India where VL and PKDL were treated separately, utilizing liposomal amphotericin B for VL and initiating Miltefosine for PKDL one month after the initial VL treatment [ 14 ]. Our patient was also first treated with a single dosage of Liposomal Amphotericin B (10 mg/kg body weight) for relapse visceral leishmaniasis, followed by Miltefosine (2.5 mg/kg/daily) 50 mg twice a day for 12 weeks for PKDL (Fig.…”
Section: Patient Presentationmentioning
confidence: 99%